Copy number variations on chromosome 12q14 in patients with normal tension glaucoma - Fingert, John H.; Robin, Alan L.; Stone, Jennifer L.; Roos, Ben R.; Davis, Lea K.; Scheetz, Todd E.; Bennett, Steve R.; Wassink, Thomas H.; Kwon, Young H.; Alward, Wallace L.M.; Mullins, Robert F.; Sheffield, Val C.; et al. (Human molecular genetics, 2011)
We report identification of a novel genetic locus (GLC1P) for normal tension glaucoma (NTG) on chromosome 12q14 using linkage studies of an African-American pedigree (maximum non-parametric linkage score = 19.7, max LOD score = 2.7). Subsequent comparative genomic hybridization and quantitative polymerase chain reaction (PCR) experiments identified a 780 kbp duplication within the GLC1P locus that is co-inherited with NTG in the pedigree. Real-time PCR studies showed that the genes within this duplication [TBK1 (TANK-binding kinase 1), XPOT, RASSF3 and GNS] are all expressed in the human retina. Cohorts of 478 glaucoma patients (including 152 NTG patients), 100 normal control subjects and 400 age-related macular degeneration patients were subsequently tested for copy number variation in GLC1P. Overlapping duplications were detected in 2 (1.3%) of the 152 NTG subjects, one of which had a strong family history of glaucoma. These duplications defined a 300 kbp critical region of GLC1P that spans two genes (TBK1 and XPOT). Microarray expression experiments and northern blot analysis using RNA obtained from human skin fibroblast cells showed that duplication of chromosome 12q14 results in increased TBK1 and GNS transcription. Finally, immunohistochemistry studies showed that TBK1 is expressed in the ganglion cells, nerve fiber layer and microvasculature of the human retina. Together, these data link the duplication of genes on chromosome 12q14 with familial NTG and suggest that an extra copy of the encompassed TBK1 gene is likely responsible for these cases of glaucoma. However, animal studies will be necessary to rule out a role for the other duplicated or neighboring genes.